Alteration of Basilar Artery Rho-Kinase and Soluble Guanylyl Cyclase Protein Expression in a Rat Model of Cerebral Vasospasm following Subarachnoid Hemorrhage. (29th May 2014) - Wang, Chih-Jen; Lee, Pei-Yu; Wu, Bin-Nan; Wu, Shu-Chuan; Loh, Joon-Khim; Tsai, Hung-Pei; Chung, Chia-Li; Kassell, Neal F.; Kwan, Aij-Lie
Abstract : Background and Purpose . The vasoconstrictor endothelin-1 (ET-1) has been implicated in the pathogenesis of cerebral vasospasm following subarachnoid hemorrhage (SAH). Previous results showed that CGS 26303, an endothelin converting enzyme (ECE) inhibitor, effectively prevented and reversed arterial narrowing in animal models of SAH. In the present study, we assessed the effect of CGS 26303 on neurological deficits in SAH rats. The involvement of vasoactive pathways downstream of ET-1 signaling in SAH was also investigated. Methods . Sprague-Dawley rats were divided into five groups (n = 6 /group): (1) normal control, (2) SAH, (3) SAH+vehicle, (4) SAH+CGS 26303 (prevention), and (5) SAH+CGS 26303 (reversal). SAH was induced by injecting autologous blood into cisterna magna. CGS 26303 (10 mg/kg) was injected intravenously at 1 and 24 hr after the initiation of SAH in the prevention and reversal protocols, respectively. Behavioral changes were assessed at 48 hr after SAH. Protein expression was analyzed by Western blots. Results . Deficits in motor function were obvious in the SAH rats, and CGS 26303 significantly improved the rate of paraplegia. Expressions of rho-kinase-II and membrane-bound protein kinase C- δ and rhoA were significantly increased, while those of soluble guanylyl cyclase α 1 and β 1 as well as protein kinase G were significantly decreased in the basilar artery of SAH rats. Treatment with CGS 26303 nearly normalized these effects. Conclusions . These results demonstrate that the rhoA/rho-kinase and sGC/cGMP/PKG pathways play pivotal roles in cerebral vasospasm after SAH. It also shows that ECE inhibition is an effective strategy for the treatment of this disease.